2016
DOI: 10.1186/s12929-016-0254-3
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells (MSCs) as skeletal therapeutics–an update

Abstract: Mesenchymal stem cells hold the promise to treat not only several congenital and acquired bone degenerative diseases but also to repair and regenerate morbid bone tissues. Utilizing MSCs, several lines of evidences advocate promising clinical outcomes in skeletal diseases and skeletal tissue repair/regeneration. In this context, both, autologous and allogeneic cell transfer options have been utilized. Studies suggest that MSCs are transplanted either alone by mixing with autogenous plasma/serum or by loading o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 144 publications
3
38
0
1
Order By: Relevance
“…An application of mesenchymal stem cell (MSC)‐based cell therapy demonstrated encouraging results in the treatment of cancer, autoimmunity, neuronal disorders, and the control of inflammation during organ transplantation (El‐Badri, Maheshwari, & Sanberg, ; Kariminekoo et al, ; Kean, Lin, Caplan, & Dennis, ; Menon, Shi, & Carroll, ). Several clinical trials have demonstrated the profound capacity of MSCs to regenerate and repair various tissues (Lerman, Alotti, Ume, & Péault, ; Ma, Tan, Zhang, & Fu, ; Saeed et al, ). Previously, the role of MSCs as well as of other immune effector cells was proved in the therapy of infectious diseases including TB (Joshi, Chelluri, & Gaddam, ; Parida et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…An application of mesenchymal stem cell (MSC)‐based cell therapy demonstrated encouraging results in the treatment of cancer, autoimmunity, neuronal disorders, and the control of inflammation during organ transplantation (El‐Badri, Maheshwari, & Sanberg, ; Kariminekoo et al, ; Kean, Lin, Caplan, & Dennis, ; Menon, Shi, & Carroll, ). Several clinical trials have demonstrated the profound capacity of MSCs to regenerate and repair various tissues (Lerman, Alotti, Ume, & Péault, ; Ma, Tan, Zhang, & Fu, ; Saeed et al, ). Previously, the role of MSCs as well as of other immune effector cells was proved in the therapy of infectious diseases including TB (Joshi, Chelluri, & Gaddam, ; Parida et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…MSCs differentiate into multiple cell lineages such as the chondrocytes, endothelial cells and the osteoblasts . The focus of this review, however, will be on their ability to differentiate along the osteogenic pathway and how this could aid in bone regeneration in diabetes . MSCs are identified based on their surface antigens such as CD34, CD19, CD73 and CD105 .…”
Section: General Stem Cell Biologymentioning
confidence: 99%
“…In a bid to accurately identify MSC markers, a list of novel markers was compiled including CD271, GD2, SSEA4 and CD146 . MSCs are located in most tissues within the body and have immunoregulatory, anti‐apoptosis, pro‐angiogenic, prodifferentiation and induction of host cell migration capabilities …”
Section: General Stem Cell Biologymentioning
confidence: 99%
“…Znane w medycynie możliwo-ści zastosowania komórek macierzystych w dużej mierze sprowadzają się do wspomagania leczenia trudno gojących się ran [7]. Odkrycie zdolności różni-cowania się mezenchymalnych komórek macierzystych w kierunku komórek tkanki kostnej zaowocowało wprowadzeniem terapii komórkami macierzystymi w schorzeniach reumatycznych i zwyrodnieniowych stawów [8]. Najnowsze doniesienia naukowe wskazują, że zastosowanie komórek macierzystych może ułatwić odbudowę rdzenia kręgowego i pozwolić na przywrócenie sprawności sparaliżowanych kończyn [9,10].…”
Section: W St ę Punclassified